‘It was a ravage!’: lived experiences of epidemic cholera in rural Haiti - Louise C Ivers; Yodeline Guillaume; Gregory J Jerome; Ralph Ternier; Max Raymond (BMJ Global Health)
Introduction A cholera epidemic began in Haiti over 8 years ago, prompting numerous, largely quantitative research studies. Assessments of local ‘knowledge, attitudes and practices’ relevant for cholera control have relied primarily on cross-sectional surveys. The voices of affected Haitians have rarely been elevated in the scientific literature on the topic.Methods We undertook focus groups with stakeholders in the Artibonite region of Haiti in 2011, as part of planning for a public health intervention to control cholera at the height of the epidemic. In this study, we coded and analysed themes from 55 community members in five focus groups, focusing on local experiences of cholera and responses to the prevention messages.Results The majority of participants had a personal experience with cholera and described its spread in militaristic terms, as a disease that ‘attacked’ individuals, ‘ravaged’ communities and induced fear. Pre-existing structural deficiencies were identified as increasing the risk of illness and death. Knowledge of public health messages coincided with some improvements in water treatment and handwashing, but not changes in open defecation in their community, and was sometimes associated with self-blame or shame. Most participants cited constrained resources, and a minority listed individual neglect, for inconsistent or unimproved practices.Conclusion The experience of epidemic cholera in a rural Haitian community at the beginning of a major outbreak included a high burden and was exacerbated by poverty, which increased risk while hindering practice of known prevention messages. To interrupt cholera transmission, public health education must be paired with investments in structural improvements that expand access to prevention and healthcare services.